O futuro simples em Português Europeu: entre a temporalidade e a modalidade - Cunha, Luís Filipe (2019)
In this paper I discuss some semantic properties that characterise the Futuro Simples (Simple Future) in European Portuguese. Departing from examples gathered in the CETEMPúblico corpus, I claim that the Futuro Simples conveys an important range of modal meanings, particularly noticeable in contexts where a covert conditional sentence is assumed, where shared knowledge plays a particular role or where a hypothetical or conjectural reading, overlapping with the speech time, is carried out. Nevertheless, as I demonstrate, temporal information constitutes also a central feature in the semantics of this verbal form, since the Futuro Simples is perfectly compatible with contexts expressing certainty, predictable facts and accurate located future situations. Moreover, aspectual factors seem to restrict some modal interpretations ascribed to the structure under analysis. In view of its two-dimensional nature, I claim that the best analysis for the semantics of the Futuro Simples must involve temporal and modal features interacting dynamically.